Associations between triglyceride glucose-body mass index and cardiovascular, renal, hepatic and bone biomarkers in patients with type 2 diabetes: a single-center, cross-sectional study - Xu, Nan; Wu, Kunyi; La, Ting; Zhang, Ruo; Cao, Bo (Frontiers in Endocrinology, 2025)
BackgroundType 2 diabetes (T2D) is a prevalent chronic metabolic disorder with significant global health implications, characterized by elevated blood glucose levels and a cluster of cardiometabolic risk factors. The triglyceride glucose-body mass index (TyG-BMI) has emerged as a novel index for assessing insulin resistance (IR) and cardiometabolic risk in T2D patients.ObjectiveThis study aims to investigate the associations between TyG-BMI and the characteristics of cardiovascular, renal, hepatic and bone biomarkers in T2D patients, particularly in the context of Cardiovascular-Kidney-Metabolic (CKM) syndrome.MethodsWe conducted a single-center, cross-sectional study involving 2,981 T2D patients. We assessed TyG-BMI and its correlations with the incidence of cardiovascular events, as well as bone, renal, and hepatic biomarkers. The study included 29 clinical characteristics of T2D patients to understand the progressive nature of T2D complications and the potential of TyG-BMI as a risk assessment tool.ResultsPreliminary findings suggest a strong association between elevated TyG-BMI and increased trends of cardiovascular, renal, and hepatic, and bone biomarkers in T2D patients. The TyG-BMI showed significantly different trends among quartile subgroups for all identified key assessing indicators, indicating its potential as a convenient and effective tool for risk assessment.ConclusionThe TyG-BMI index is potentially associated with cardiovascular, renal, hepatic, and bone biomarkers in T2D patients. These findings could contribute to the development of strategies for the prevention and translational therapies of related complications in T2D patients, ultimately improving patient outcomes and reducing the burden on healthcare systems.